Broker to broker : (J. Wiley, 2006)
By providing best practice management tips with thought-provoking ideas, Broker to Broker offers invaluable guidance on virtually every aspect of our dynamic industry. The book's easy-to-read format, with in-depth supporting material available online, is an innovative approach to helping the country's brokers and managers find effective solutions to today's challenges.